The efficacy of metacognitive therapy on emotional processing components of patients with functional dyspepsia: controlled clinical trial - Batebi, Sepideh; Masjedi Arani, Abbas; Jafari, Mahdi; Sadeghi, Amir; Saberi Isfeedvajan, Mohsen; Davazdah Emami, Mohammad Hasan (Researcher Bulletin of Medical Sciences, 2022)
Background: Functional dyspepsia is characterized by a set of symptoms in the upper gastrointestinal tract due to an underlying organic cause and is one of the common causes of patients ’visits to gastroenterologists. A few researches have been conducted on the effectiveness of psychotherapy with respect to the psychological components of these patients. Therefore, the purpose of this study is to investigate the effect of metacognitive therapy on emotional processing components of these patients. Materials and Methods: In this study, 40 patients with dyspeptic symptoms were recruited after medical examination by gastroenterologists, performing H. Pylori test and undergoing endoscopy. Moreover, 20 of the patients were randomly assigned to a group for metacognitive therapy and another 20 to the control group. The Baker's emotional processing questionnaire was used at pre-treatment, post-treatment and three months after treatment for evaluating changes in patients' emotional processing styles. Finally, repeated measures analysis of variance was employed for data analysis by using SPSS 19. Results: The research data that was obtained by repeated measures analysis of variance indicated statistically significant differences in three emotional processing scales in metacognitive therapy group compared to the control group at pre-treatment, post-treatment and three months after treatment. Conclusion: Compared to the control group, the metacognitive therapy of functional dyspepsia patients was more effective in the short- and long-term for coping with difficulty in emotional recognition and experience, difficulty in emotional control and expression as well as inadequate emotional processing